КЕЎИЛ САНДЫҒЫНАН ЗЕР ШАШҚАН ШАЙЫР (Т.Мәтмуратовтың өмири ҳәм дөретиўшилиги) - Алламбергенов, К. (ILIM hám JÁMIYET, 2020)
The given article deals with analyses of life, work, lyrics, epics of well-know representative of the karakalpak literature of XX century T.Matmuratov. Poet is described in wide range as thinker, lyrics, humanist and patriot. Author on the basis of the given qualities proves in details that poet was lyrics and philosopher, who leads people to kindnese and pure soul.